Principals as Innovative Leaders in the Independent Learning Transformation - Citraningsih, Diningrum (Jurnal Inovatif Manajemen Pendidikan Islam, 2025)
The Merdeka Belajar program, initiated by the Minister of Education, Nadiem Makarim, encourages principals to adjust the curriculum and supporting programs to create an independent, creative, and collaborative learning environment. The purpose of this study was to determine the role of the principal as an innovator in the transformation of independent learning at SDIT Mufidatul 'Ilmi. The study used a qualitative method in which researchers collected data through semi-structured interviews, non-participant observation, and documentation. The results of the study showed that in carrying out the role of an innovative principal, it was done by creating creative and student-oriented learning management policies and utilizing existing facilities in the school environment, as a facilitator for teacher competency development, building a democratic school culture, and liaising with external stakeholders for school progress. In addition, the principal provides opportunities for teachers and education personnel to improve their skills through various activities at school and with school partners. Collaboration with parents of students and the local government is also continuously carried out to maintain positive synergy and create good and harmonious relationships. This study reveals the role of the principal as an innovator in the Merdeka Belajar policy, highlighting learning management strategies, teacher competency development, and collaboration with stakeholders.